Punched Nerve Syndrome: Ultrasonographic Appearance of Functional Vascular Nerve Impairment - Loizides, A.; Peer, S.; Plaikner, M.; Djurdjevic, T.; Gruber, H. (Ultraschall in der Medizin - European Journal of Ultrasound, 2012)
Purpose: The mechanical impact of a neighboring vessel on a “punched” nerve segment is thought to be one possible cause of compression neuropathy but has not been proven definitively. We report on 9 subjects with unclear clinical mononeuropathies in whom we could clearly define peripheral nerve impairment by such vessels on real-time high-resolution ultrasound (HRUS). Materials and Methods: Nine subjects with unclear mononeuropathy based on clinical neurological examination were referred to our department for HRUS assessment. The shape, inner and outer echotexture, size and diameter, and overall integrity of these nerves were assessed including an exact analysis of the surrounding soft tissues to search for potentially extraneural pathology. This included duplex imaging to identify even tiny atypical vascular structures. Results: In all patients duplex HRUS showed the pulsatile and “punching” character of the relevant vessels and the direct mechanical impact of these vessel. The involved nerve segments appeared enlarged with a hypoechoic change of echotexture including at least partial masking of their inner fascicular texture. Conclusion: Although rare, a “punching” vessel can be the cause of a compression neuropathy. Therefore, duplex HRUS must be included in every HRUS examination of patients with otherwise unclear mononeuropathy.
Keywords: nervous-peripheral; ultrasound; ultrasound color Doppler; ultrasound power Doppler